Human capital, labour market outcomes, and horizontal inequality in Guatemala - Carla Canelas; Rachel M. Gisselquist (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
With the second largest indigenous population by percentage in Latin America, Guatemala is an important case for understanding horizontal inequality and indigenous politics. This paper presents new analysis of survey data, allowing for consideration both of indigenous and ladino populations, as well as of ethno-linguistic diversity within the indigenous population. Overall, our analysis illustrates both the depth and persistence of horizontal inequalities in educational and labour market outcomes, and a broad trend towards greater equality. Earnings gaps have been reduced by, among other factors, improved educational outcomes. Ethnic groups also show distinct patterns of wages and wage gaps, and there is evidence of a 'sticky floor' effect at the lower ends of the income spectrum affecting some groups more than others. Our findings suggest that the focus on the indigenous/non-indigenous divide found in much of the economic literature on Latin America obscures meaningful diversity within the indigenous population. We posit that further consideration of such within-group diversity has implications for broader theories of ethnic politics, and in particular for understanding the comparative weakness of indigenous political mobilization in Guatemala at the national level.
Keywords: J22; J31; J71; 330; inequality; ethnicity; schooling; earnings; Guatemala